Peran Shopping Enjoyment Dalam Memediasi Pengaruh Perceived Quality Dan Store Atmosphere Terhadap Impulsive Buying Konsumen Oh!Some - Putra P, Komang Widhya Sedana; Setianingsih, Made Apriani; Lestari, Ni Putu Nina Eka; Mulyadi, Made (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This scientific study aims to further explore the perceived quality and atmosphere of stores that influence impulsive buying, considering the role of shopping enjoyment among OH!SOME consumers. The background of this study is based on the limitations and differences in findings from previous studies, as well as differences in focus in discussing the relationship between variables. The approach used is quantitative, with the research object focused on OH!SOME consumers in Denpasar City. Since the population size is not precisely known, the sample size was determined using Hair et al's formula, resulting in 120 respondents. Data was collected using an online questionnaire via Google Form, applying a five-point Likert scale. The data obtained was processed using SmartPLS 3.0 software. Based on the data processing results, it was found that perceived quality and store atmosphere have a positive and significant effect on impulsive purchasing, both directly and through shopping enjoyment as a mediating variable. The results of this study are focused on providing benefits and a more comprehensive understanding of how consumers' perceived quality and store environment atmosphere can shape a pleasant shopping experience while encouraging impulsive purchasing behavior among OH!SOME consumers.